Using carbamide for preparing nitrogen-doped graphene hydrogels to enhance supercapacitor performance. (20th March 2020) - Su, Weifeng; Gao, Dongming; Zheng, Weichao; Lu, Feng; Liu, Jingyan; Chen, Xiangcheng; Sha, Ou; Chen, Ling
ABSTRACT: In this paper, nitrogen-doped graphene hydrogel (NGH) has been synthesised by chemically reducing aqueous graphene oxide (GO) solution in the presence of carbamide.Its nitrogen content reaches 8.97 at%. It exhibits a 3D porous network structure with pore sizes of about 2 to 4 μm comparable to the graphene hydrogel (GH) prepared without nitrogen source. Meanwhile, the NGH shows same hierarchical mesoporous structure with dominant pore size about 2–5 nm as the GH's. Besides, its specific surface area (132.8 m 2 g −1 ) is higher than that of the GH (122.9 m 2 g −1 ). The NGH can deliver an enhanced specific capacitance of 199.80 F g −1 at 2 A g −1 compared to that of the GH (142.23 F g −1 ). In addition, the NGH can retain 62.6% of specific capacitance from 2 to 50 A g −1 . The NGH also can maintain 97% of its initial specific capacitance after 20, 000 cycles at 10 A g −1 .